2018
DOI: 10.1590/s0004-2803.201800000-33
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Lipids During HCV Treatment: Virus Action or Medication?

Abstract: -Background -The interaction between serum lipids and C virus infection is well known, as are serum lipid levels in the Peg-IFN / RBV-based treatment. However, with direct action antivirals (DAAs) this behavior is still unclear. Objective -To compare serum lipids levels between patients treated with Peg-IFN/RBV and DAAs and to evaluate lipids in sustained virological response (SVR) with DAAs. Methods -Retro prospective study comparing the behavior of total cholesterol (TC), low-density lipoprotein (LDL) and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Nevertheless the treatment itself might not have a negative impact on glucose metabolism [26][27][28] . There are also strong data showing an increase in total cholesterol and LDL levels 24,26,29 , which we could not confirm, probably due to the small test group. The post-treatment increase in CAP and LDL was highest among patients with low pre-treatment steatosis 25 and did not affect individuals with the highest initial levels of LDL 24 .…”
Section: Discussioncontrasting
confidence: 57%
“…Nevertheless the treatment itself might not have a negative impact on glucose metabolism [26][27][28] . There are also strong data showing an increase in total cholesterol and LDL levels 24,26,29 , which we could not confirm, probably due to the small test group. The post-treatment increase in CAP and LDL was highest among patients with low pre-treatment steatosis 25 and did not affect individuals with the highest initial levels of LDL 24 .…”
Section: Discussioncontrasting
confidence: 57%
“…Reports on the effect of DAA treatment on blood TGs are, however, contradictory. An increase in blood TGs was described in some studies [19][20][21], whereas other studies could not identify a change in TG levels by DAA therapy [3,22,23] or even observed a decline [24,25]. It was also reported that elimination of HCV led to a rise in serum TGs in HCV patients with fibrosis stages F0-F2 but not in those with advanced disease [21,26].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is well accepted that the effective elimination of HCV causes a rise in serum LDL and cholesterol [ 17 , 47 , 48 , 49 , 50 ]. All but CE 14:0, CE 14:1, CE 15:1 and CE 16:1 were significantly increased at therapy end.…”
Section: Discussionmentioning
confidence: 99%